MEASUREMENT OF THE RISK LEVEL AND INDIVIDUAL SHARE PROFIT BY USING A HISTORICAL APPROACH TO THE VALUE AT RISK (VaR) METHOD ON THE TOP 10 BEST COMPANY STOCK IN RTI PERIOD 2023 - Perli Iswanto; Aditya Rian Ramadhan (International Journal Multidisciplinary Science, 2023)
Research has been conducted to measure individual risk with profit level using the Value at Risk (VaR) approach. The research method used to analyze the data with refers to the Historical Simulation Model approach. The data used is the daily asset return data obtained from the daily closing price of shares during the January 2022 period. The results of the VaR method approach are Historical Simulation. The model shows NICL (PT Pam Mineral Tbk)stock with a risk of 30 million to 40 million. The measurement results show that if the funds invested are Rp. 500,000,000.00 with a 95% confidence level, the period is 1 year 248 days from published stock data of each company.